The Impact of Chasless Society and Financial Technology on the Consumptive Lifestyle of Students of the University of Muhammadiyah Palu - Chusnul Khatima Nawir Risah; Guasmin; Umar (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze the effect of Cashless Society and Financial Technology on the consumptive lifestyle of students at Universitas Muhammadiyah Palu. This research employs a quantitative approach using multiple linear regression analysis. The sample consists of 246 students selected through a specific sampling technique. Data were collected questionnaires and analyzed using simultaneous testing (F-test) and partial testing (t-test). The findings reveal that, simultaneously, Cashless Society and Financial Technology have a significant effect on students' consumptive lifestyle. However, partially, Cashless Society does not have a significant effect, whereas Financial Technology has a significant influence on the consumptive lifestyle. These results indicate that ease of access, service flexibility, and fintech features such as paylater and digital promotions are more dominant in driving consumptive behavior compared to non-cash payment systems. In conclusion, Financial Technology is identified as the primary factor influencing students' consumptive lifestyle in the digital era. Therefore, enhancing financial literacy is essential to ensure that the use of financial technology can be managed wisely.